STRATEGI PROJECT BASED LEARNING UNTUK MENINGKATKAN KREATIVITAS SISWA - Jesika Ramasuci; Reisya Shabilla; Hermalia Putri (Sindoro: Cendikia Pendidikan, 2025)
Project-based learning (PBL) strategies have been shown to enhance creativity in students at various levels of education. PBL encourages students to actively participate and collaborate in a learning process that involves innovation and problem solving. This method allows students to work together in groups to design, plan, and implement projects related to the subject matter. This allows them to apply the knowledge and skills they have learned. Students are given the freedom to show their creativity, come up with unique solutions, and create products that others can see. They do this by exploring ideas, experimenting, and reflecting. Studies show that PBL enhances students’ creative skills in addition to increasing their desire to learn and their engagement in the learning process. Therefore, PBL strategies can be a useful tool to help students become creative and prepare them to face real-world challenges. Keywords: strategy, project based learning, creativity